Stability and controllability of motion of dynamic systems at a distance from the equilibrium positions - Sparavalo , M. K. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We prove theorems that establish the connection between the stability and the controllability of the motion far off from the equilibrium positions and the existence of homogeneous ω-attractors, ω-repellers, and ω-shunts in the extended state space of dynamical systems.